2021
DOI: 10.1111/jvs.12997
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative and reproductive phenology in a tropical grassland–savanna–forest gradient

Abstract: Question: Climate, particularly precipitation, is the primary factor driving tropical plant phenology because of its relevant role in regulating water availability. However, differences in soil physicochemical properties can also drive resource availability, potentially affecting plant phenology, especially under similar environments in terms of rainfall regime. We determined whether the seasonality and synchrony of the vegetative and reproductive phenophases differ along a grassland-savanna-forest gradient un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…Second, we found a significant phylogenetic signal for seed dispersal season, while seed dispersal season in the Cerrado (Escobar et al 2021) and other phenological events in the campo rupestre (Zanetti et al 2020;Oliveira et al 2021) have not shown such signal. As a result, seed dispersal season is the only phenophase that has shown a significant phylogenetic signal in the Brazilian rock outcrop vegetation, potentially because of an intense evolutionary pressure towards germination timing in these harsh ecosystems, where water is even scarcer than in the Cerrado (Oliveira et al 2021), thus may create stronger selective pressures for establishment.…”
Section: Seed Functional Traits Are Phylogenetically Clustered In Bra...mentioning
confidence: 52%
See 4 more Smart Citations
“…Second, we found a significant phylogenetic signal for seed dispersal season, while seed dispersal season in the Cerrado (Escobar et al 2021) and other phenological events in the campo rupestre (Zanetti et al 2020;Oliveira et al 2021) have not shown such signal. As a result, seed dispersal season is the only phenophase that has shown a significant phylogenetic signal in the Brazilian rock outcrop vegetation, potentially because of an intense evolutionary pressure towards germination timing in these harsh ecosystems, where water is even scarcer than in the Cerrado (Oliveira et al 2021), thus may create stronger selective pressures for establishment.…”
Section: Seed Functional Traits Are Phylogenetically Clustered In Bra...mentioning
confidence: 52%
“…Still, the authors tested and measured the phylogenetic signal of this trait using Bloomberg's K, an index known to be highly sensitive to sample sizes and incomplete phylogenetic background, and that provides divergent results to Pagel's l (Münkemüller et al 2012). Second, we found a significant phylogenetic signal for seed dispersal season, while seed dispersal season in the Cerrado (Escobar et al 2021) and other phenophases in the campo rupestre (Zanetti et al 2020;CS Oliveira et al 2021) have not shown such signal. As a result, seed dispersal season is the only phenophase that has shown a significant phylogenetic signal in the Brazilian rock outcrop vegetation, potentially as a result of an intense evolutionary pressure towards germination timing in these ecosystems, where water is even more scarce than in the Cerrado (CS .…”
Section: Seeds Functional Traits Are Phylogenetically Conserved In Br...mentioning
confidence: 70%
See 3 more Smart Citations